2003
DOI: 10.2337/diacare.26.2.547
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Is Reduced in Lean Subjects With Type 2 Diabetes in Bangladesh

Abstract: Cross-sectional studies of the combined intima-media wall thickness (IMT) of the carotid arteries performed in type 1 diabetic patients show partly contradictory results with regard to variables that are associated with the IMT. Therefore, we observed the IMT progression in a longitudinal study with two follow-ups: 1) after 2-3 years (mean 2.5 Ϯ 0.4); and 2) after 4 -8 years (mean 6.3 Ϯ 1.4).A total of 65 type 1 diabetic patients (24 men, 41 women) with Յ40 years of age and a diabetes duration of Ն2 years at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 7 publications
4
8
2
Order By: Relevance
“…There are a lot of conflicting results regarding the increase or decrease in leptin levels among T2D patients [49,50]. In our study, no difference in leptin levels was found between non-obese T2D patients and non-obese controls.…”
Section: Resultscontrasting
confidence: 61%
“…There are a lot of conflicting results regarding the increase or decrease in leptin levels among T2D patients [49,50]. In our study, no difference in leptin levels was found between non-obese T2D patients and non-obese controls.…”
Section: Resultscontrasting
confidence: 61%
“…These results suggest that low leptin levels may be attributed to insignificant relationship between BMI and leptin in diabetic male patients ( p = 0.842) and significant relationship between BMI and leptin in nondiabetic males ( p = 0.009). Abu-Sayeed et al [30] found that lean diabetic patients have shown low leptin levels. These results were also reported by many other researchers [14, 31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the sympathetic nervous system has been found to be involved in leptin-mediated regulation of bone mass (Takeda et al 2002). Serum levels of leptin, a hypothalamic hormone, are abnormal in type-2 diabetes patients (Abdelgadir et al 2002, Fischer et al 2002, Sayeed et al 2003. Since autonomic neuropathy is common in diabetes, both the neuropathy and abnormal leptin levels may contribute to osteopathy.…”
Section: Discussionmentioning
confidence: 99%